2021
DOI: 10.1589/jpts.33.722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isometric contraction of the quadriceps on the hardness and blood flow in the infrapatellar fat pad

Abstract: This study aimed to clarify the influence of the isometric contraction of the quadriceps (ICQ) with low intensity on the circulation in the infrapatellar fat pad (IFP). [Participants and Methods] The participants were 7 males and 5 females, with an average age of 21.5 ± 1.4 years. IFP hardness was measured using shear wave ultrasound elastography and Biodex. Tissue oxygenation was measured via near-infrared spectroscopy using oxygenated hemoglobin (O2Hb), deoxygenated hemoglobin (HHb), and total hemoglobin (cH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, this penetration depth would likely result in the deep fat pad, which has its own vascular supply, to be included in the measurement. Previous studies reported that, while this fat pad has a limited blood supply that may be accounted in the NIRS monitoring, its blood flow is minimally responsive to exercise 38 . Therefore, we feel confident our results truly represent the response of the tendons and the fad pad did not influence the final outcomes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, this penetration depth would likely result in the deep fat pad, which has its own vascular supply, to be included in the measurement. Previous studies reported that, while this fat pad has a limited blood supply that may be accounted in the NIRS monitoring, its blood flow is minimally responsive to exercise 38 . Therefore, we feel confident our results truly represent the response of the tendons and the fad pad did not influence the final outcomes.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies reported that, while this fat pad has a limited blood supply that may be accounted in the NIRS monitoring, its blood flow is minimally responsive to exercise. 38 Therefore, we feel confident our results truly represent the response of the tendons and the fad pad did not influence the final outcomes. Additionally, the NIRS set-up used in the present study is unable to differentiate between changes in blood flow of the tendon and skin.…”
Section: Resultsmentioning
confidence: 74%
“…Kitagawa et al 17 evaluated the IFP thickness change ratio in anterior cruciate ligament (ACL)-reconstructed knees at 90° and 10° of knee flexion and defined the thickness change ratio as dynamic. Katayama et al 18 measured the IFP’s shear modulus in healthy adults using shear-wave elastography and evaluated IFP stiffness. In addition, Satake et al 19 reported that they observed a percentage of maximal fibrosis to increase as the shear wave speed of IFP increased.…”
Section: Introductionmentioning
confidence: 99%